(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The use of energy-efficient gas blocks in residential buildings, along with accelerating the construction process in the late twentieth and early twenty-first centuries, significantly reduces the load on the load-bearing structures of the building, significantly increases the cost of the building and increases the quality of the building. became one. In this environment, where modern technology is still evolving and new and convenient forms are being developed, the use of energy-efficient gas blocks in our current construction is not only in our opinion, but also in the interests of other researchers. Therefore, in the near future, further improvement of the use of energy-efficient gas units is one of the most pressing issues in the development of construction technology. The article describes the real experience, scientific research and results of our country in improving these technological processes.